PENGARUH MOTIF PENGGUNAAN SECOND ACCOUNT INSTAGRAM TERHADAP EKSISTENSI DIRI (STUDI EKSPLANATIF PADA MAHASISWA AKTIF ILMU KOMUNIKASI UPN "VETERAN" JAKARTA) - Nadila Halystia Nataya (2021)
The advancement of internet and smartphone technology is increasingly visible, resulting in the birth of social media, one of which is Instagram. The existence of more than one Instagram account is a place for self-existence which is called the Second Instagram Account. The research objective was to prove the magnitude of the influence of the motive of using the second Instagram account on self-existence (an explanatory study of the active students of Communication Science UPN "Veteran" Jakarta). The research method used is quantitative by testing Uses and Gratification Theory on 104 active students of communication science at UPN Jakarta. The sample technique used probability sampling, while data processing used a questionnaire. Motive is measured based on dimensions according to McQuail motive: Individual motives in media use, while self-existence is measured based on the characteristics of an individual having an existence in the book Psychotherapy and Existentialism and Smith's "What Matters". The research results from the Correlation Test show a significance value of 0.00 which indicates a correlation because it is located at <0.05. The calculated r coefficient of 0.733 indicates that there is a strong correlation. The regression test results show that the motive for using a second Instagram account for self-existence is positive. The results of the coefficient of determination show that there is an influence of 53.72% between the motives of the second Instagram account user on existence. These results are reinforced by the results of hypothesis testing which states that Ho is rejected and Ha is accepted, meaning that there is an influence between the motive for using a second Instagram account on self-existence. The conclusion of the study is that the motive for using a second Instagram account affects users to self-existent, especially active students of communication science at UPN "Veteran" Jakarta